1994
DOI: 10.1172/jci116953
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic and ischemic hypoxia exacerbate brain injury associated with metabolic encephalopathy in laboratory animals.

Abstract: Hypoxemia is a major comorbid factor for permanent brain damage in several metabolic encephalopathies. To determine whether hypoxia impairs brain adaptation to hyponatremia, worsening brain edema, we performed in vitro and in vivo studies in cats and rats with hyponatremia plus either ischemic or hypoxic hypoxia. Mortality with hypoxic hypoxia was 0%; with hyponatremia, 22%; and with hyponatremia + hypoxia, 100%. Hyponatremia in cats produced brain edema, with a compensatory decrease of brain sodium. Ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 37 publications
(55 reference statements)
3
36
0
1
Order By: Relevance
“…The high hippocampal involvement may be related to its high vulnerability to the neurotoxic effects of osmotic derangements 49 and systemic stresses in general. 50,51 In reviewed cases, contrast enhancement associated with ODS lesions was reported in 1 patient, 23 which has also been reported in some cases of hyponatremia. 52 Although inconsistently found, contrast enhancement is in agreement with the pathophysiologic changes observed in experimental models of ODS, in which BBB disruption occurs secondary to osmotic stress and is thought to be one of the leading factors in pathogenesis of ODS.…”
Section: Osmotic Demyelination Syndromementioning
confidence: 73%
“…The high hippocampal involvement may be related to its high vulnerability to the neurotoxic effects of osmotic derangements 49 and systemic stresses in general. 50,51 In reviewed cases, contrast enhancement associated with ODS lesions was reported in 1 patient, 23 which has also been reported in some cases of hyponatremia. 52 Although inconsistently found, contrast enhancement is in agreement with the pathophysiologic changes observed in experimental models of ODS, in which BBB disruption occurs secondary to osmotic stress and is thought to be one of the leading factors in pathogenesis of ODS.…”
Section: Osmotic Demyelination Syndromementioning
confidence: 73%
“…The authors also showed a failure of the adaptive mechanisms of the brain to chronic hyponatraemia in a number of the postmenopausal patients. This failure of cerebral adaptation may have been related to hypoxia, which has been shown in animal studies to impair the cerebral adaptive mechanisms to hyponatraemia (Vexler et al, 1994).…”
Section: Effects Of Hyponatraemiamentioning
confidence: 99%
“…It appears that ischemic hypoxia severely impairs the brain's adaptive mechanisms during hyponatremia by reducing cerebral oxygen availability. It may be an important comorbid factor in the morbidity associated with hyponatremic encephalopathy 22 . Bilateral basal ganglia lesions such as these may be seen in association with hypoxia, but in this case, no respiratory disturbance, cardiac arrest, or hypotension had occurred.…”
Section: Discussionmentioning
confidence: 99%